Kontradiksi Potensi dan Realisasi Pajak Reklame - Dwi Astuty Arfah; Eka Ariaty Arfah; Muhammad Reza Ramdani (Jur. Akuntansi, Politeknik Negeri Malang, 2021)
Research examines rates of the billboard tax increase regional revenue, for that purpose of research to analyze the determination of the billboards tax rate in increasing the original income of the District (PAD) Maros Regency. The research approach uses a qualitative descriptive, data in the research derived from the data on realization of billboards through strict supervision and through counseling to billboard taxpayers about the urgency of the billboard tax for the regions. Results finding that the process of determining billboards tax rate could increase the PAD in Maros district. Research can inform decision making for the local government of maros in setting standards with respect to the advertisement tax. AbstrakPenelitian ini meneliti tentang tarif pajak billboard dalam upaya memaksimalkan pendapatan asli daerah, arah artikel ini untuk memahami penetapan tarif pajak periklanan. Pendekatan penelitian menggunakan kualitatif deskriptif. Hasil penelitian menunjukkan bahwa proses penetapan tarif pajak reklame dapat meningkatkan PAD di kabupaten maros melalui pengawasan yang ketat serta melalui penyuluhan kepada wajib pajak reklame tentang urtgensi pajak reklame bagi daerah. Kontribusi penelitian ini dapat menjadi informasi pengambilan keputusan bagi pemerintah daerah Maros dalam penetapan standar sehubungan dengan pajak reklame.